Combination product of dermal matrix, human mesenchymal stem cells, and timolol promotes diabetic wound healing in mice. (28th July 2020) - Yang, Hsin‐ya; Fierro, Fernando; So, Michelle; Yoon, Daniel J.; Nguyen, Alan Vu; Gallegos, Anthony; Bagood, Michelle D.; Rojo‐Castro, Tomas; Alex, Alan; Stewart, Heather; Chigbrow, Marianne; Dasu, Mohan R.; et al.
Abstract: Diabetic foot ulcers are a major health care concern with limited effective therapies. Mesenchymal stem cell (MSC)‐based therapies are promising treatment options due to their beneficial effects of immunomodulation, angiogenesis, and other paracrine effects. We investigated whether a bioengineered scaffold device containing hypoxia‐preconditioned, allogeneic human MSCs combined with the beta‐adrenergic antagonist timolol could improve impaired wound healing in diabetic mice. Different iterations were tested to optimize the primary wound outcome, which was percent of wound epithelialization. MSC preconditioned in 1 μM timolol at 1% oxygen (hypoxia) seeded at a density of 2.5 × 10 5 cells/cm 2 on Integra Matrix Wound Scaffold (MSC/T/H/S) applied to wounds and combined with daily topical timolol applications at 2.9 mM resulted in optimal wound epithelialization 65.6% (24.9% ± 13.0% with MSC/T/H/S vs 41.2% ± 20.1%, in control). Systemic absorption of timolol was below the HPLC limit of quantification, suggesting that with the 7‐day treatment, accumulative steady‐state timolol concentration is minimal. In the early inflammation stage of healing, the MSC/T/H/S treatment increased CCL2 expression, lowered the pro‐inflammatory cytokines IL‐1B and IL6 levels, decreased neutrophils by 44.8%, and shifted the macrophage ratio of M2/M1 to 1.9 in the wound, demonstrating an anti‐inflammatory benefit. Importantly, expression of the endothelial marker CD31 was increased by 2.5‐fold with this treatment. Overall, the combination device successfully improved wound healing and reduced the wound inflammatory response in the diabetic mouse model, suggesting that it could be translated to a therapy for patients with diabetic chronic wounds. Abstract :